Long-term ethanol intoxication reduces inflammatory responses in rats - E.M. Carvalho; G.A.C. Brito; B.B.G.P. Pessoa; R.A. Ribeiro; F.R. Capaz (Brazilian Journal of Medical and Biological Research, 2005)
The anti-inflammatory effects of long-term ethanol intoxication were determined during ethanol treatment and withdrawal on the basis of neutrophil and eosinophil migration, hind paw edema and mast cell degranulation. Male Wistar rats (180-200 g, around 2 months of age) were exposed to increasing concentrations of ethanol vapor over a 10-day period. One group was evaluated immediately after exposure (treated group - intoxicated), and another was studied 7 h later (withdrawal group). Ethanol inhalation treatment significantly inhibited carrageenan- (62% for the intoxicated group, N = 5, and 35% for the withdrawal group, N = 6) and dextran-induced paw edema (32% for intoxicated rats and 26% for withdrawal rats, N = 5 per group). Ethanol inhalation significantly reduced carrageenan-induced neutrophil migration (95% for intoxicated rats and 41% for withdrawn rats, N = 6 per group) into a subcutaneous 6-day-old air pouch, and Sephadex-induced eosinophil migration to the rat peritoneal cavity (100% for intoxicated rats and 64% for withdrawn rats, N = 6 per group). A significant decrease of mast cell degranulation was also demonstrated (control, 82%; intoxicated, 49%; withdrawn, 51%, N = 6, 6 and 8, respectively). Total leukocyte and neutrophil counts in venous blood increased significantly during the 10 days of ethanol inhalation (leukocytes, 13, 27 and 40%; neutrophils, 42, 238 and 252%, respectively, on days 5, 9 and 10, N = 7, 6 and 6). The cell counts decreased during withdrawal, but were still significantly elevated (leukocytes, 10%; neutrophils, 246%, N = 6). These findings indicate that both the cellular and vascular components of the inflammatory response are compromised by long-term ethanol intoxication and remain reduced during the withdrawal period.